How businesses strategize for sustainability and overcome barriers within different economic paradigms - La Motte,Sofie (Master Thesis Series in Environmental Studies and Sustainability Science, 2024)
Industrial society is the reason for the rising global ecological crisis, and companies are a primary contributor to this trend. To change this course, companies must transform along with society’s green transition. In the academic debate of economics and sustainability, various competing economic paradigms suggest how to steer society towards a sustainable transformation. Based on theoretical historical reasoning, three paradigms can be recognised: Techno-Optimism, Green Growth and Post-Growth. This study creates an analytical framework, identifying structural approaches and indicators for business strategies within each paradigm. Utilising this framework, the study performs an explorative multi-case study to understand the sustainable strategy in three dissimilar companies and the internal and external barriers they face in relation to the paradigms. The results reveal that, in the process of engaging in sustainability, companies explore solutions across different paradigms. The structural surroundings constitute barriers in the form of competitiveness and growth; however, corporate values significantly influence how these barriers are overcome in the search for more sustainable practices.
Keywords: Sustainability Strategy; Barriers; Company; Economic Paradigms; Sustainability Science